2010
DOI: 10.1002/art.27382
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of connective tissue growth factor in fibroblasts in vivo promotes systemic tissue fibrosis

Abstract: Objective Connective tissue growth factor (CTGF) is a cysteine-rich secreted matricellular protein involved in wound healing and tissue repair. Enhanced and prolonged expression of CTGF has been associated with tissue fibrosis in humans. However, questions remain as to whether CTGF expression alone is sufficient to drive fibrosis. This study was undertaken to investigate whether CTGF alone is sufficient to cause fibrosis in intact animals and whether its effects are mediated through activation of transforming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 27 publications
9
141
0
Order By: Relevance
“…Sonnylal et al (20,21) demonstrated that targeted overexpression of CTGF in lung fibroblasts disrupts lung structure and induces fibrosis which affects both lung fibroblasts and epithelial cells. Our previous studies showed that targeted overexpression of CTGF in AT II cells not only disrupts alveolar and vascular development but also induces interstitial fibrosis and vascular remodeling (12).…”
Section: Discussionmentioning
confidence: 99%
“…Sonnylal et al (20,21) demonstrated that targeted overexpression of CTGF in lung fibroblasts disrupts lung structure and induces fibrosis which affects both lung fibroblasts and epithelial cells. Our previous studies showed that targeted overexpression of CTGF in AT II cells not only disrupts alveolar and vascular development but also induces interstitial fibrosis and vascular remodeling (12).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive expression of CTGF in fibroblasts is sufficient to cause accelerated diffuse tissue fibrosis in vivo [40]. The Ets factor, Fli1, may be of central importance in this pathway.…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
“…Ivkovic et al (35) have shown that global knockout of CTGF results in respiratory failure and immediate death in newborn mice suggesting that endogenous CTGF in lung cells are important for embryonic lung development and newborn lung function. Sonnylal et al (31,32) demonstrated that targeted overexpression of CTGF in lung fibroblasts induces fibrosis which affects both lung fibroblasts and epithelial cells indicating that fibroblast-derived CTGF results in lung fibrosis via both autocrine Articles Shafieian et al…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these cells expressed mesenchymal markers such as α-SMA, fibronectin, and vimentin, suggesting EMT-like changes. Sonnylal et al, have demonstrated that CTGF causes EMT-like cell fate in vivo and in vitro in the lung (31,32). They used transgenic mice with mesenchymal overexpression of CTGF driven by the collagen 1a2 promoter as well as lung epithelial cells lines A549 and SV40-T2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation